2014
DOI: 10.1016/j.ccr.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Regulatory Network Analysis Identifies a Synergistic Interaction between FOXM1 and CENPF that Drives Prostate Cancer Malignancy

Abstract: Summary To identify regulatory drivers of prostate cancer malignancy, we have assembled genome-wide regulatory networks (interactomes) for human and mouse prostate cancer from expression profiles of human tumors and of genetically engineered mouse models, respectively. Cross-species computational analysis of these interactomes has identified FOXM1 and CENPF as synergistic master regulators of prostate cancer malignancy. Experimental validation shows that FOXM1 and CENPF function synergistically to promote tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
392
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 307 publications
(414 citation statements)
references
References 40 publications
21
392
0
1
Order By: Relevance
“…The corresponding human PC interactome was produced by ARACNe analysis of a set of gene expression profiles from~200 patient-derived PC samples, representing the full spectrum of disease progression. Comparison of the human and murine interactomes, using a novel algorithm, revealed that 70% of the regulatory programs in PC are highly conserved between these 2 species, including those of 2 synergistic master regulators (MRs) of progression to aggressive disease (forkhead box protein M1 and centromere protein F), inferred by the Master Regulator Inference algorithm (MARINa) [7,[12][13][14][15], and experimentally validated both in mouse and in human tissue. However, the analysis also showed that 30% of the programs are not conserved, including those representing a few PC-related genes that would thus be unlikely to produce patient-relevant results if studied or targeted in a murine context.…”
Section: Developing Human To Mouse To Human Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…The corresponding human PC interactome was produced by ARACNe analysis of a set of gene expression profiles from~200 patient-derived PC samples, representing the full spectrum of disease progression. Comparison of the human and murine interactomes, using a novel algorithm, revealed that 70% of the regulatory programs in PC are highly conserved between these 2 species, including those of 2 synergistic master regulators (MRs) of progression to aggressive disease (forkhead box protein M1 and centromere protein F), inferred by the Master Regulator Inference algorithm (MARINa) [7,[12][13][14][15], and experimentally validated both in mouse and in human tissue. However, the analysis also showed that 30% of the programs are not conserved, including those representing a few PC-related genes that would thus be unlikely to produce patient-relevant results if studied or targeted in a murine context.…”
Section: Developing Human To Mouse To Human Approachesmentioning
confidence: 99%
“…To address this impasse and to avoid findings that are idiosyncratic to a specific biological model but fail to generalize to the human context, we propose a cross-species approach that has been highly successful in the study of human malignancies [4]. Specifically, we propose assembling accurate, genome-wide regulatory models for both mouse models of AD and for their human counterpart to assess systematically the subset of the regulatory logic of AD neurons that is conserved or divergent between the two species.…”
Section: Developing Human To Mouse To Human Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify potential TFs that regulate each phenotype, we used the master regulator interference algorithm (MARINa), which has been used to identify master regulators for human high-grade glioma, murine prostate cancer, and normal formation of germinal centers (40)(41)(42). We created a network of TFs and their targets by combining transcriptional and genomic data from multiple databases (43)(44)(45)(46).…”
Section: Benign and Cancer Gene Expression Profiles From The Same Epimentioning
confidence: 99%